KESEPAKATAN TIDAK TERTULIS PADA HUKUM PERIKATAN DAN HUKUM BISNIS - Hapsari, Nia Puspita; Rambuni, Arraya Rambu; Syaharani, Regina Pinkan; Padaloka, Rocky Putra Maya (Lex Jurnalica, 2024)
An unwritten agreement or oral agreement is an agreement made only based on theagreement of the parties orally without any written evidence. The legal implicationsof this unwritten agreement are an important concern in legal practice. Article1320 KUHPerdata stipulates that for the validity of an agreement four conditionsare required: agreement of the parties, capacity to make an obligation, a certainmatter, and a lawful cause. In addition, evidence by witnesses, testimony,confession, and oath. However, written evidence is not the only evidence that canbe used in proving an agreement. The court can also accept other valid evidence toprove the existence of an agreement, such as electronic evidence, testimony, andassumptions. Therefore, in legal practice, it is important to understand the legalimplications of unwritten agreements and the ways to prove them in court.Keywords: Implications, Unwritten Agreement, Business Law